Physical Responses Following Post-Partum Administration of Rectal Misoprostol in RSKIA Kota Bandung West Java, Indonesia - Slamet Riyanto; Restuning Widiasih (Journal of Nursing Care, 2018)
Background Postpartum haemorrhage is identified as one of main causes of maternal mortality especially in low income countries including Indonesia. The use of rectal misoprostol is a considerable intervention to prevent postpartum haemorrhage. However, administering misoprostol would cause various considerable responses that need intensive observation to prevent high risk condition of post-partum women. Limited studies in Indonesia assessed responses of post-partum women’s after misoprostol administration. This study aimed to identify physical responses of post-partum women after misoprostol administration. Methods, This descriptive quantitative study involved 30 post-partum women. They were chosen using consecutive sampling technique. The data collection instruments were an observation form and a semi-structured interview form. Using those instruments women’s physical responses observed on the minute of 15, 30, 45, 60, 90 and the hour of 2, 3, and 4 after post- partum. The data were analysed using frequency distribution. Results The study found that there were different physical responses of women after rectal misoprostol administration including nausea, vomiting, diarrhoea, headache and fever, especially in the minute of 15 and the hour of 2. The most prominent physical responses were nausea, and followed by headache and fever. Conclusion This study finding is a significant information for health professionals especially nurses. Nurses could develop an anticipatory guide in anticipating any effects that may risk to postpartum patients.